Long‐term (48 weeks) effectiveness, safety, and tolerability of erenumab in the prevention of high‐frequency episodic and chronic migraine in a real world: Results of the EARLY 2 study - Barbanti, Piero; Aurilia, Cinzia; Cevoli, Sabina; Egeo, Gabriella; Fofi, Luisa; Messina, Roberta; Salerno, Antonio; Torelli, Paola; Albanese, Maria; Carnevale, Antonio; Bono, Francesco; D'Amico, Domenico; et al. (Headache, 2021)
Objective To evaluate the long‐term effectiveness, safety, and tolerability of erenumab in a real‐world migraine population, looking for putative predictors of responsiveness. Background Erenumab proved to be effective, safe, and well tolerated in the prevention of episodic migraine (EM) and chronic migraine (CM) in long‐term extension studies of double‐blind, placebo‐controlled trials in patients with no more than two (EM) or three (CM) prior preventive treatment failures. Methods A 48‐week, multicenter, longitudinal cohort real‐life study was conducted at 15 headache centers across eight Italian regions between December 20, 2018 and July 31, 2020. We considered all consecutive patients with high‐frequency episodic migraine (HFEM) or CM aged 18–65 years. Each patient was treated with erenumab 70 mg, administered monthly. The dose was switched to 140 mg in nonresponders and in responders who had become nonresponders for at least 4 weeks. Change in monthly migraine days (MMDs) or monthly headache days (MHDs) at Weeks 45–48 compared with baseline was the primary efficacy endpoint. Secondary endpoints encompassed variation in monthly analgesic intake, achievement of a ≥50%, ≥75%, or 100% reduction in migraine or headache days, and any change in the Visual Analogue Scale (VAS) and Headache Impact Test‐6 scores (HIT‐6) during the same time interval. Results A total of 242 patients with migraine received at least one dose of erenumab 70 mg and were considered for safety analysis, whereas 221 received a monthly erenumab dose for ≥48 weeks and were included in the effectiveness and safety analysis set. All patients had previously been treated unsuccessfully with ≥3 migraine‐preventive medication classes. From baseline to Weeks 45–48, erenumab treatment reduced MMD by 4.3 ± 5.3 (mean ± SD) in patients with HFEM, and MHD by 12.8 ± 8.9 (mean ± SD) in subjects with CM. VAS and HIT‐6 scores were decreased by 1.8 ± 1.9 (mean ± SD) and 12.3 ± 11 (mean ± SD) in HFEM, and by 3.0 ± 2.2 (mean ± SD) and 13.1 ± 11.2 (mean ± SD) in CM. Median monthly analgesic intake passed from 11.0 (interquartile range [IQR] 10.0–13.0) to 5 (IQR 2.0–8.0) in HFEM and from 20.0 (IQR 15.0–30.0) to 6.0 (IQR 3.8–10.0) in CM. The ≥50% responders were 56.1% (32/57) in HFEM and 75.6% (124/164) in CM; ≥75% responders were 31.6% (18/57) and 44.5% (73/164); and 100% responders were 8.8% (5/57) and 1.2% (2/164), respectively. At Week 48, 83.6% (137/164) of patients with CM had reverted to EM. Erenumab was safe and well tolerated. Responsiveness to erenumab was positively associated with cutaneous allodynia (OR: 5.44, 95% CI: 1.52–19.41; p = 0.009) in HFEM. In patients with CM, ≥50% responsiveness was positively associated with male sex (OR: 2.99, 95% CI: 1.03–8.7; p = 0.044) and baseline migraine frequency (OR: 1.12, 95% CI: 1.05–1.20; p = 0.001) and negatively associated with psychiatric comorbidities (OR: 0.37, 95% CI: 0.15–0.87; p = 0.023) and prior treatment failures (OR: 0.77, 95% CI: 0.64–0.92; p = 0.004). Conclusions Long‐term (48‐week) erenumab treatment provides sustained effectiveness, safety, and tolerability in real‐life patients with HFEM or CM with ≥3 prior preventive treatment failures. The dose of 140 mg was required in most patients along the study and should be taken into consideration as the starting dose. Allodynia (in HFEM), male sex, and baseline migraine frequency (in CM) might represent positive responsiveness predictors. Conversely, psychiatric comorbidities and multiple prior preventive treatment failures could be negative predictors in patients with CM.